Post-Reform Cinema Public Space on Detik.com News Portal - Amin Shabana; Harmonis Harmonis; Zahwa Indira; Mutia Andini (Komunikator, 2022)
Film festivals are public cultural spheres that arose quickly after the fall of the New Order. The rise of film festival activities was covered by the Indonesian mass media, particularly online media. Detik.com is an example of online media that is currently a public reference, including witnessing the development of film festivals in post-reformation Indonesia. The primary goal of this research is to examine the representation of the public sphere in a film festival article written by Detik.com. This study chose an explanatory qualitative approach based on media framing theory. From its inception until 2019, Detik.com was Indonesia’s first news portal, publishing 894 articles on film festivals. The analysis knife employs several major theories, including Public Space (Habermas), Film Festival (De Valck), and news framing (De Vreese). To strengthen the article, the sources cited are also the most comprehensive, consisting of government groups (e.g., Executive and DPR) and non-government groups (filmmakers, festival managers, academics, religious groups, and spectators). When comparing the scale of implementation, national film festivals are mostly covered, namely 28 film festivals and eight film festivals. During the post-reform era, the most news framing film festivals are generic issues (33 festivals) versus 14 festivals that fall into the category of specific issue framing.